Efektifitas Masyarakat Sipil di Kenagarian Kab. Lima Puluh Kota dalam Mewujudkan Pemilihan Umum Demokratis - Wendra Yunaldi Zainal; Jasman Nazar; Yenni Fitri Z; Irwan Irwan (Integritas: Jurnal Antikorupsi, 2021)
The strength of civil society with cultural values ​​as cultural awareness that characterizes the social order of Kenagarian Situjuah Batua and Kenagarian Sarilamak has the potential to determine the direction of democratic elections. This study aims to answer how the function, involvement and role of civil society in Kenagarian Kab. Fifty Cities carry out democratic general elections without money politics through democracy awareness movements based on customary values ​​(local wisdom). With the KPK's strategic role in preventing the development of money politics in general elections, civil society groups play an important role together with the KPK in creating the implementation of democratic elections. Through a phenomenological approach with inductive analysis. The research found that civil society in Kenagarian Situjuah Batua, which is homogeneous and consistent with the customary system, is more effective in campaigning against money politics, compared to civil society in Kenagarian Sarilamak, whose community structure is heterogeneous. Referring to these two experiences, a custom-based cultural approach with the strength of respected community leaders has turned out to be very effective in creating anti-corruption groups in the midst of society. With the results of this study, efforts can be made to take an original cultural approach to prevent the growing use of money politics in the implementation of democratic elections.